Swimming exercise modifies oxidative stress in skeletal and cardiac muscles of diabetic rats - F. Pio, Talita; E. Orzari, Lucas; A. Alves, Armindo; C. L. Silveira, Paulo; A.M. Esquisatto, Marcelo; A. M. de Andrade, Thiago; Felonato, Maíra; A. Dalia, Rodrigo (Revista Saúde & Diversidade, 2022)
Introduction: Oxidative stress is a key factor leading to the deterioration of diabetes. Oxidative stress exacerbates diabetes and induction of the activity of the antioxidant system may be required to prevent this effect. Objetive: The aim of the present study was to evaluate the redox state in the skeletal and cardiac muscles in a diabetes rat model subjected to swimming exercise for 4 weeks. Methods: Wistar rats were divided into four groups: untrained control (C), trained control (T), untrained alloxan-induced diabetes (D), and trained alloxan-induced diabetes (TD). The redox state of the skeletal and cardiac muscles was assessed by analyzing TBARS, -SH groups, H2O2 production, and SOD and catalase activity. The total number of cardiomyocytes and the total area of collagen fibers in the cardiac muscle were measured by histomorphometry. Results: In the Soleus muscles, the TD group showed increased H2O2 levels and catalase activity compared to the T group, and SOD activity compared to the D group. Regarding the red gastrocnemius, the TD group presented higher SOD and lower catalase activities than the D group. Regarding the cardiac muscle, the TD group presented lower TBARS and higher levels of -SH groups and catalase activity than the D group. Swimming exercise decreased hyperglycemia and reduced pathology, as evidenced by the reduced number of cardiomyocytes and the area of collagen fibers. Conclusion: Swimming exercise in diabetic rats controlled hyperglycemia and oxidative damage, and the reduced fibrosis in the cardiac muscle of diabetic rats.